Warum weinen? Eine Geschichte des Trauerns im liberalen Italien (1850-1915) - Buchner, Moritz (Bibliothek des Deutschen Historischen Instituts in Rom, 2018)
Demonstrating feelings of grief was of great importance in the elite culture of liberal Italy. At the same time, mourning the dead flew in the face of societal trends toward secularization. The study analyzes the background of this ambivalent situation of conflict, examines the role of religion and nation in relation to death, discusses the relationship between body and emotions, and shows how grief was expressed across space.